Patty's Toxicology 2001
DOI: 10.1002/0471435139.tox086
|View full text |Cite
|
Sign up to set email alerts
|

Ethers of Ethylene Glycol and Derivatives

Abstract: There are currently seven U.S. manufacturers of ethers and other derivatives of ethylene glycol (EG), diethylene glycol (DEG), and higher glycols. Five of them are members of the American Chemistry Council (ACC) Glycol Ethers' Panel. The glycol ethers most commonly encountered industrially are colorless liquids that have mild ethereal odors. Alkyl glycol ethers are manufactured in a closed, continuous process by reacting ethylene oxide with an anhydrous alcohol in the presence of a suitable catalyst.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 276 publications
0
17
0
Order By: Relevance
“…Most glycol ethers have a halflife of less than 1 h and most acidic metabolites have a half-life of less than 24 h (INSERM 1999;Boatman 2001;Boatman and Knaak 2001). However, the halflives of MAA and EAA are 77 h and 42 h, respectively (Groeseneken et al 1988(Groeseneken et al , 1989.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most glycol ethers have a halflife of less than 1 h and most acidic metabolites have a half-life of less than 24 h (INSERM 1999;Boatman 2001;Boatman and Knaak 2001). However, the halflives of MAA and EAA are 77 h and 42 h, respectively (Groeseneken et al 1988(Groeseneken et al , 1989.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on laboratory animals and humans have shown that some EG ether derivatives, such as monomethyl ether (EGME) and monoethyl ether (EGEE), have adverse effects on reproduction and development and are toxic to the bone marrow, whereas butyl ether (EGBE) has haemolytic effects (for reviews see ECETOC 1995;INSERM 1999;Boatman 2001;Boatman and Knaak 2001). The toxic effects of glycol ethers are associated with the formation of alkoxycarboxylic acid metabolites (Miller et al 1983;Foster et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous toxicological reports have shown that various ethylene glycol ethers, particularly the short-chain ethylene glycol methyl ether (EGME) and ethylene glycol ethyl ether (EGEE), have pronounced adverse effects on sperm production and quality in the rat, mouse and rabbit. [9][10][11] The toxic effects of glycol ethers are thought to be mediated by their alkoxycarboxylic metabolites, which are rapidly eliminated by urines. 12 13 However, very few studies were conducted in human populations.…”
mentioning
confidence: 99%
“…Blood from humans, pigs, dogs, cats, and guinea pigs was insensitive to hemolysis induced by BAA at the concentrations used. In sensitive species of common laboratory animals including rats, mice, and rabbits, BE produces a characteristic toxicity that is revealed clinically by the appearance of hemoglobinuria and pathologically by changes in a variety of blood parameters (Boatman & Knaak, 2001). Regardless of the route of administration, hemolysis was regarded as the primary cause of death in rats (Gingell et al, 1998;Sivaroa & Mehendale, 1995).…”
Section: Humans Are Insensitive To the Hemolytic Effects Of Bementioning
confidence: 99%